Praxis, Freedom and Affections: On the “supra-nature” of the Will in Duns Scotus - Ginocchio, David González; Lecón, Mauricio (Scripta Mediaevalia, 2022)
In dealing with the will, Scotus and Aristotle are not so far that Scotus himself denies their continuity, nor so close that he avoids reinterpreting the Aristotelian notion of prohaíresis in light of the Christian philosophy of freedom. His reinterpretaion consists in conceiving the will as a rational power, that is to say, free, and the intellect as a natural power. In this paper we will insist on this continuity and discontinuity in the following order: 1) we will show to what extent Scotus’s will goes beyond intellection and, in that sense, “nature”, focusing on the cases of incontinence and negligent omissions; 2) we will trace the structure of the Scotist will, following and answering Barnwell; 3) we will later study the freedom of the will, as Scotus understands it, mainly in his commentary on Metaphysics IX and, finally, 4) we will return to the influence of passions and the habits on the will for determining what is good. Our purpose is to show that Scotus takes up Aristotelian formulations to show how the will is a properly rational appetite, i.e. pace Aristotle, not properly an appetite.